Edmée Chandon : femme pionnière, scientifique invisible. Les ressorts de l’injustice épistémique dans le champ astronomique du premier XXe siècle - Charly Pellarin-Régis (Genre & Histoire)
Edmée Chandon (1885-1944) started working at the Paris Observatory in 1908 and was appointed assistant astronomer in 1912, making her France’s first professional woman astronomer. On 26th March 1930, she became the first French woman to defend her thesis in mathematics. This paper aims at understanding how two movements, epistemic injustice and the myth of the pioneer, meet around the figure of Edmée Chandon and how they end up concealing her scientific contribution. The Edmée Chandon Collection, held at the Paris Observatory library and recently listed, helps in assessing her part in scientific production, shedding the media’s myth of the pioneer, as well as the epistemic injustice conveyed by gender stereotypes. The paper’s first two parts analyse this process of invisibilisation. Then the third and last part, with the help of her work archives tries to deconstruct the epistemic injustice in order to shed light on Edmée Chandon’s contribution to the scientific production of the first part of the twentieth century.